Determinasi Pembelian Makanan Halal Melalui Platform Digital: Kesadaran Halal Sebagai Variabel Mediasi - Muhammad Anwar Fathoni; Faizi Faizi; Retna Sari (ITB AAS INDONESIA Surakarta, 2023)
This study aims to investigate Halal Awareness in mediating the effect of the Halal Logo, Subjective Norms, and Online Customer Rating on consumer behavior in purchasing halal food through digital platforms. This study uses a quantitative approach with a sample of 100 Muslim respondents spread across several major cities in Indonesia. The data collected in the study were analyzed using the Partial Least Square (PLS) method. This study found that the Halal Logo did not have a direct influence on consumer purchasing decisions, but the Halal Logo was able to influence consumer purchasing decisions through the mediation of Halal Awareness. Subjective Norms and Halal Awareness have a direct effect on consumer purchasing decisions, only Online Customer Rating has no influence on consumer purchasing decisions, either directly or indirectly.